2021
DOI: 10.1101/2021.06.10.447945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ovule siRNAs methylate protein-coding genes in trans

Abstract: 24-nt small interfering siRNAs maintain asymmetric DNA methylation at thousands of euchromatic transposable elements in plant genomes in a process call RNA-directed DNA Methylation (RdDM). Although this methylation occasionally causes transcriptional silencing of nearby protein-coding genes, direct targeting of methylation at coding sequences is rare. RdDM is dispensable for growth and development in Arabidopsis, but is required for reproduction in other plant species, such as Brassica rapa. 24-nt siRNAs are p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Siren loci generate 24‐nt siRNAs, first identified for their abundance in rice endosperm (Grover et al., 2020; Rodrigues et al., 2013). These loci map predominantly to genic and intergenic regions rather than transposable elements (Burgess et al., 2022). The siren correspond to approximately 200 loci in Brassica rapa and are present in diverse other angiosperms (Grover et al., 2020; Rodrigues et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Siren loci generate 24‐nt siRNAs, first identified for their abundance in rice endosperm (Grover et al., 2020; Rodrigues et al., 2013). These loci map predominantly to genic and intergenic regions rather than transposable elements (Burgess et al., 2022). The siren correspond to approximately 200 loci in Brassica rapa and are present in diverse other angiosperms (Grover et al., 2020; Rodrigues et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…S11, 12 ). A recent preprint reported that, in B. rapa ovules, a fraction of siren siRNAs can silence genes with sequence homology in trans via DNA methylation ( Burgess et al 2021 ). We cannot exclude that the same process might also occur in rice egg cells and zygotes, regardless of the cell type of origin of siren siRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Siren loci generate 24-nt siRNAs, first identified for their abundance in rice endosperm (Rodrigues et al, 2013;Grover et al, 2020). These loci map predominantly to genic and intergenic regions rather than transposable elements (Burgess et al, 2022).…”
Section: Hundreds Of Loci Demonstrate a 24-nt Phasing Pattern But Exc...mentioning
confidence: 99%